STUDI TENTANG KEGIATAN BELAJAR PESERTA DIDIK SMP NEGERI 35 PADANG - Murni, Sari; Arief, Asmaiwaty; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The study findings revealed that the learners learning activities in the learning process is still lacking to follow, due to the lack of motivation of learners in the learning process to follow, not the material readiness of the students in the following study, the lack of completeness of the study aids learners in the learning process to follow, less comfortably learners learning environment, learners conditions unfavorable in the following learning activities, teachers and teaching styles that are not liked by the students, and the students can not use the facilities that have been provided by the school so as not to create an atmosphere of learning or study room comfortable and conducive as possible, this is because the students are not concentrating when learning activities attributable often feel sleepy, lethargic and not in the spirit of research in the learn. The result is recommended to the various parties involved, namely the learners are expected to be able to utilize the facilities provided at the school so that learning activities can be followed properly, setting the room where the study well and clean up the place and did not chide learning in the classroom, students are also expected to be able to maintain the health conditions in the following lesson so do not bother to follow the concentration of students in learning activities in the classroom.